Respostas cardiovasculares associadas ao intervalo interséries de exercício resistido em mulheres hipertensas sob controle farmacológico - Pereira, Gilene de Jesus (2016)
Resistance exercise (RE) is indicated as a complement to aerobic exercise program to control high blood pressure. However, it is known that during RE may occur peak pressure and increased risk of cardiovascular events in hypertensive individuals. It is known that the exercise intensity, exercise volume and muscle fatigue potentiate these effects. The effects of blood pressure control and the rest time between sets have not yet been investigated. The objective of this study was to verify, in hypertensive women undergoing resistance exercise, the effects of blood pressure control and the rest time between sets (30s, 60s and 90s) the responses of systolic blood pressure (SBP) and diastolic (DBP), heart rate (HR) and double product (DP). The study included nineteen hypertensive women, mean age 58.5 ± 5.2 years and BMI 29.4 ± 4.9 kg / m2, were divided into groups: controlled (n=6), decompensated (n=8) and untreated (n=5). The subjects were submitted to the 1RM test in the leg extension and held three training sessions resistance (3x12 to 60% of 1RM knee extension). Each session was performed with different rest interval (30, 60 and 90 seconds). It used 2-way ANOVA for repeated measures with post test Tukey, establishing a significance level of p<0.05. In the control group, there was no significant difference between exercise and rest to PAD, FC and DP in any of the intervals (p>0.05), while SBP was higher than the rest, when the rest interval was 30 seconds (p=0,0204). In uncontrolled and untreated groups, there was an increase in all the variables, compared to the rest (p<0.05) independent of the rest interval. Pressure peaks reached during the exercise, in the controlled group (SBP: 171.3 ± 14 and DBP: 99.5 ± 11mmHg) were similar as compare to uncontrolled groups (216.1 ± 11 and DBP: 132.5 ± 16 mmHg) and untreated (216.8 ± 21 and DBP: 133.6 ± 13mmHg). Thus, if the hypertensive framework is not controlled, the cardiovascular stress significantly increases during the RE and the pharmacological control is shown to be effective in reducing the effort during the practice of RE. Therefore, the control condition of the hypertensive frame is more important than the rest interval for influencing the cardiovascular responses during the RE. Thus, we can suggest that effective control of the PA, through pharmacological treatment can reduce the risk of pressure peak during the practice of resistance exercise.